The decline of the Ottoman Empire and the rise of the Turkish Republic - Özoğlu, Hakan, 1964- (Edinburg)
213 sayfa
Keywords: “In the immediate aftermath of World War I, Rear Admiral Mark L. Bristol was US High Commissioner in the Ottoman Empire and later the Turkish Republic (1919–27). In reporting and examining Bristol’s official correspondence to the State Department, Hakan Özoğlu paints an alternative picture of Turkey and the transition period from empire to nation state. A key diplomat, Admiral Bristol’s observations and recommendations helped to shape US foreign policy in the Ottoman Empire, out of which the modern Middle East emerged. His actions also laid the foundations of the strategic partnership between Turkey and the US, from the Cold War years through to the 21st century“ --